TikTok Made Me Buy It: Analyzing the Influence of Content Marketing and Engagement on Generation Z's Purchase Intention - Ferdianto, Raditya; Nurcahyo, Satria Avianda; Wahyuni, Eka Renny Noviati; Aisyah, Siti (CV. Strata Persada Academia, 2024)
This study aims to examine the influence of content marketing and customer engagement on the purchase intentions of Generation Z users on the TikTok platform in Central Java, utilizing a quantitative methodology and the SmartPLS version 3.29 analysis tool. The sample of this study included 200 Tiktok Platform Users aged 16-28 years in the Central Java region. Data was collected through a questionnaire focused on content marketing, customer engagement, and purchase intention. An analysis was performed to examine the correlation between content marketing and customer engagement regarding buy intention and to evaluate the mediation function of consumer engagement in the correlation between content marketing and purchase intention. The outcomes of this study indicate that content marketing and customer engagement have a positive and significant impact on purchase intention, with customer engagement acting as a mediating variable in the relationship between content marketing and purchase intention. Furthermore, creating content by paying attention to Reader Cognition and sharing motivation, persuasion, and decision-making factors with Generation Z on the Tiktok platform will increase enthusiasm, attention, sharing, and learning in customer engagement so that it will encourage transactional interest or referential interest or preferential interest or an exploratory interest in customers.